Recombination in Coronaviruses, with a Focus on SARS-CoV-2 - Daniele Focosi; Fabrizio Maggi (Viruses, 2022)
Recombination is a common evolutionary tool for RNA viruses, and coronaviruses are no exception. We review here the evidence for recombination in SARS-CoV-2 and reconcile nomenclature for recombinants, discuss their origin and fitness, and speculate how recombinants could make a difference in the future of the COVID-19 pandemics.